A high performance team delivering a state-wide Intensive Care Clinical Information System (ICCIS) for NSW. - Kowal, D.; Jacques, T.; Butcher, R.; Abbenbroek, B.; Weisbrodt, L.; Dellagiacoma, T.; Gattas, D. (Australian Critical Care, 2015)
The intensive Care Clinical Information System (ICCIS) Program commenced in 2011 and is the largest program of its type globally. ICCIS, initiated by intensive care clinicians, is being delivered collaboratively by the Agency for Clinical Innovation (ACI) Intensive Care Services Network, eHealth ICCIS Program Team and iMDsoft. Underpinning this high performance team is strong collaboration, clinical engagement, communication and leadership for the design, build and delivery of the ICCIS solution. The Clinical Engagement Model was embedded in the development of ICU business requirements to inform the selection, design and build of the ICCIS solution for NSW. A proactive communications and engagement plan was implemented, the Agile Project Management model adopted, and organisational change management framework developed. The ACI ICCIS Working Group was established in 2013 to provide clinical leadership for the project and production phases. Formation of ACI ICCIS WG Subject Matter Expert Reference Groups for reporting, pharmacy, technical, research, paediatric and neonatal requirements followed. Clinician engagement has increased throughout the ICCIS Program with a 400% increase in active voluntary clinician participation from the initial clinical evaluation group (n= 18) to the establishment of the ACI ICCIS Working Group and specialty subgroups (n = 70) in the design and build phase. Effective engagement with the broader ICU community through proactive communications was demonstrated by an increase in viewer hits from 400 in 12 months (2013 first video release) to 480 in two weeks with the second video release in 2014. The success of the ICCIS Program's clinical leadership and engagement demonstrates the impact of a high performance collaborative team. The success of the ICCIS Program is contingent on active engagement of intensive care clinicians to deliver ICCIS on behalf of clinicians for the benefit of patient care and clinician satisfaction.